Orthodontic and implant-prosthetic treatment of hypodontia: a report of two cases - Rafałowicz, Barbara; Wagner, Leopold (Journal of Stomatology, 2018)
Congenital absence of maxillary tooth germs in adults is a serious problem. Basic treatment includes orthodontic and/or implantoprosthetic procedures. The aim of the study is to present possible therapeutic procedures in the treatment of hypodontia of maxillary teeth in complex anatomical and biological conditions in adult patients. The study presents two cases of orthodontic treatment and implant-prosthetic rehabilitation of maxillary hypodontia. In the first case, after obtaining space with fixed braces, a decision was made to insert a mini implant at the site of the missing upper right lateral incisor, on which a porcelain-fused-to-metal (PFM) crown was fixed. In the second case, after the expected effect of orthodontic treatment was achieved, the missing upper right lateral incisor and the missing upper right first bicuspid were restored with a PFM bridge, while the other missing upper left bicuspid was restored with a PFM bridge based on the implant. In the presented cases, effective orthodontic treatment was followed by an implant-prosthetic technique with the use of mini implants and fixed dentures, which allowed morphological, functional, and esthetic restoration of missing teeth. Both patients have had the restorations for 10 years and so far, have reported no functional or esthetic problems. The applied orthodontic treatment and implant-prosthetic rehabilitation fulfilled the esthetic and functional needs of the patients. It must be emphasized that a treatment of an adult person with hypodontia may be disturbed by unforeseen circumstances, which may require corrections of the initial treatment plan.